Cultural Variations in the Development of Mind Reading. (31st October 2014) - Slaughter, Virginia; Perez‐Zapata, Daniel
Abstract In this article, we summarize research on the development of mind reading in different cultural contexts. Much of this work has focused on the mind‐reading concept of false belief, that is, children's ability to predict what an actor is likely to do based on what he or she thinks. In all cultures tested, individuals acquire this skill in childhood, but differ cross‐culturally in the age of acquisition. Studies exploring the development of other aspects of mind reading reinforce the conclusion that culture influences when and how children understand the mind.